(untitled) (Journal of Medical & Health Sciences Review, 2025)
The purpose of the study was to observe the clinical features and complications of dengue infection. Admitted patients to the medical ward with dengue virus infection were studied in the General Hospital Penang, Malaysia. A total of 756 patients were enrolled from January 2007 to December 2007. The clinical features were evaluated and compared in terms of age groups. The patients were distributed in four different age groups. Children ≤18 years, young age groups 19 to 36 years, adults 37 to 54 years and the elderly age group ≥55 years old. The differences in clinical features between children and adults require further evaluation to identify and recognise the substantial factors involved. Ascites, jaundice, and pleural effusion are the complications of dengue, which require early identification in association with thorough monitoring and basic medical support to save the lives of dengue patients.